THEORETICAL AND PRACTICAL ASPECTS OF JUDICIAL RECONCILIATION IN REPUBLIC OF KAZAKHSTAN - Erchikova, Perizat; Myrzakhanova, Marzan (Administrative and Criminal Justice, 2019)
Conflict as a clash of opposing interests, opinions, attitudes, goals, and positions is one of the everyday phenomena inherent in human society. It may be different depending on its scale and vary in the range from domestic quarrel to geopolitical confrontation between nuclear powers. In this case, the conflict itself, in spite of the negative attitude of narrow-minded to it, is a rather neutral phenomenon, its positive and negative effects are associated not only with the conflict itself, as to the method of its settlement. At the same time, the rational settlement of the conflict, such as through a constructive dialogue, it becomes the driving force of human progress, it helps to get the relationship on a completely different level.